Restriction enzyme fingerprinting of enterobacterial plasmids: a simple strategy with wide application. - Platt, D. J. (Cambridge University Press, 1986)
Restriction enzyme fingerprints were generated from purified plasmid DNA from 324 clinical isolates that belonged to 7 enterobacterial genera and 88 single plasmids in Escherichia coli K 12 according to the following strategy. Purified plasmid DNA was digested with PstI. The number of fragments detected in a 0.8 agarose gel was used to determine which 2 of 6 restriction enzymes including PstI was most likely to provide a fingerprint comprising sufficient fragments to ensure specificity but sufficiently few to allow easy visual assessment and minimize coincidental matching. When PstI produced greater than 20 fragments, EcoRI and HindIII were used; when PstI generated less than 6 fragments Bsp 1286 and AvaII were used and SmaI was employed when between 6 and 20 fragments were obtained from PstI digests. Using a minimum of 12 fragments from a combination of 2 enzymes as the criterion for characterizing a strain/plasmid, satisfactory 2-enzyme fingerprints were obtained from 87% of the strains and plasmids studied using PstI and no more than two additional enzymes per strain. Of the remaining 54 strains, 51 harboured only small plasmids (less than 10 kb) and 3 produced satisfactory fingerprints when digested with a fourth enzyme.